UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PADA ANAK KELOMPOK A DENGAN MENGGUNAKAN MEDIA FLASHCARD DI RA AL HUDA MALANG TAHUN PELAJARAN 2024/2025 - Syafarotul Ma'idah; Nurhayati (LPPM IAD Probolinggo, 2025)
The purpose of this study was to use flashcard media to improve the reading skills of group A children at RA Al Huda, Malang. Early childhood education is an important phase in child development because here children build basic skills such as reading. Text comprehension and recognition of letters, words, and sentences are components of early childhood reading learning. In this study, a case study approach was used to evaluate the experiences of teachers and children with flashcard media. Observation, interviews, and documentation were used to collect data. The results showed that the use of flashcard media significantly increased children's interest and reading skills. As a visual learning tool, flashcards offer an interactive learning method that encourages students to work together and makes learning more fun. Flashcards also help children remember and understand new concepts better. Therefore, this study suggests the use of flashcard media as a great way to improve early childhood reading skills. Keywords: Early Childhood; Learning Methods; Flashcard Media